(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2007)
The aim of this research is to determine whether and, if so, what role traditional African culture plays in the economic development of the continent. The following steps are taken: (1)As an introduction the urgent need of economic development for Africa is underlined by way of a brief review of the extreme poverty of 50% of its population. (2)Then the myths as well as real reasons for Africa’s underdevelopment as well as the possible solutions suggested by the prominent development economist, J.F. Sachs, are reviewed. (3)The fact that he does not acknowledge the important role of culture in economic development leads to an critical investigation of the rationalistic philosophy underlying his economic theories. (4)This is followed by a number of African writers who identify different aspects of their traditional culture as negative for economic development. (5)Finally the results are briefly summarised in the conclusion.